Impact of evidence-based pedagogical approach on clinical reasoning among undergraduate physical therapy students - Pavithra Venugopal; Hariharasudan Subramanian; Manoj Abraham Manoharlal (Journal of Current Research in Scientific Medicine)
Background: Various educational methods have been used by professional physical therapy teachers for their students. Since physical therapy includes both theory and practical, students may need to critically think about each patient’s intervention based on the stage of their illness. It is necessary to teach and assess students’ clinical reasoning abilities, so as to deal with the patients. The aim of the study was to find the impact of evidence-based pedagogical approach on clinical reasoning among undergraduate physical therapy students. Materials and Methods: The study was conducted in our institution and it was a pre- and post-test experimental study design. Forty students in their 3rd year of undergraduate physical therapy (BPT) degree program were randomly assigned to experimental group (evidence-based pedagogical approach, n = 20) and to control group (traditional pedagogical approach, n = 20). They were assessed with Self-Assessment of Clinical Reflection and Reasoning (SACRR), clinical reasoning assessment tool (CRAT) (3 domains), and multiple-choice test, at the baseline and after 4 weeks of training. Data were analyzed using an independent t-test. Results: Experimental group showed a significant difference in SACRR (t = 3.4446, P < 0.05), CRAT (Content knowledge and Conceptual reasoning domains showed significant differences with t = 3.2110; 2.7973, P<0.05, but Procedural knowledge domain was not significant with t = 0.7791, P<0.05), and multiple-choice test (t = 5.8538, P < 0.05) scores than the control group. Conclusions: The use of evidence-based pedagogical approach may be more effective than the traditional pedagogical approach for improving clinical reasoning among undergraduate physical therapy students.